2003
DOI: 10.1128/aac.47.7.2093-2099.2003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Resistance ofPseudomonas aeruginosato Quaternary Ammonium Compounds and Expression of Outer Membrane Protein OprR

Abstract: The adaptation mechanism of Pseudomonas aeruginosa ATCC 10145 to quaternary ammonium compounds (QACs) was investigated. A P. aeruginosa strain with adapted resistance to QACs was developed by a standard broth dilution method. It was revealed that P. aeruginosa exhibited remarkable resistance to N-dodecylpyridinium iodide (P-12), whose structure is similar to that of a common disinfectant, cetylpyridinium chloride. Adapted resistance to benzalkonium chloride (BAC), which is commonly used as a disinfectant, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…1). This degree of adaptation to biocide in continuous culture system is some fourfold greater than that observed for strains adapted using a simple serial batch culture (Tabata et al, 2003). Furthermore, in this study, developed strains showed stable inheritance of the characteristic when cultured in the absence of BKC selection pressure.…”
Section: Resultsmentioning
confidence: 74%
“…1). This degree of adaptation to biocide in continuous culture system is some fourfold greater than that observed for strains adapted using a simple serial batch culture (Tabata et al, 2003). Furthermore, in this study, developed strains showed stable inheritance of the characteristic when cultured in the absence of BKC selection pressure.…”
Section: Resultsmentioning
confidence: 74%
“…(i) Many numerically important drain bacteria were nonsusceptible to QAC. QAC tolerance has been described previously (22) and relates to the physiology of the bacteria (48), particularly the expression of efflux pumps (8,9). (ii) Another possibility is the acknowledged nonsusceptibility of biofilms to antimicrobials (2,18,28,45).…”
Section: Resultsmentioning
confidence: 99%
“…4B). Although the specific function of the outer membrane lipoprotein remains unclear, a previous study reported increased expression of this gene in response to QACs and suggested that it functions either as an efflux pump or to physically enhance membrane integrity against QACs (36). Sterol carrier proteins transfer steroids across cellular membranes (37), and enoyl-acyl carrier reductase is involved in the fatty acid elongation cycle (38); thus, both genes modulate membrane fluidity, permeability, and thickness and could play a role in alleviating BAC toxicity by enhancing cell membrane integrity.…”
Section: Discussionmentioning
confidence: 99%